2004
DOI: 10.1007/s00122-004-1846-y
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis underlying female sterility detected in hybrid breakdown in a Japonica?Indica cross of rice (Oryza sativa L.)

Abstract: Epistasis is considered to be a primary genetic basis of hybrid breakdown. We found novel epistatic genes causing hybrid breakdown in an intraspecific cross of cultivated rice (Oryza sativa L.). F2 progeny derived from a cross between a Japonica variety, Asominori, and an Indica variety, IR24, showed segregation of high sterility for seeds, even though the reciprocal F1 hybrids showed about 60% seed fertility. Backcross populations (BC3F2, BC3F3), obtained from repeated backcrossing with Asominori, showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
51
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 25 publications
6
51
1
Order By: Relevance
“…In this system, Kubo and Yoshimura (2002) have genetically mapped both partners of a two-locus incompatibility with major effects on hybrid viability and fertility. Recently, the same authors mapped a different three-locus genetic incompatibility that exclusively affects hybrid female fertility (Kubo and Yoshimura 2005). The genetic basis of hybrid male sterility between species of Oryza also appears simple: a major sterility factor from O. glaberrimo causes male gamete abortion against an O. sativa genetic background (Sano 1990).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this system, Kubo and Yoshimura (2002) have genetically mapped both partners of a two-locus incompatibility with major effects on hybrid viability and fertility. Recently, the same authors mapped a different three-locus genetic incompatibility that exclusively affects hybrid female fertility (Kubo and Yoshimura 2005). The genetic basis of hybrid male sterility between species of Oryza also appears simple: a major sterility factor from O. glaberrimo causes male gamete abortion against an O. sativa genetic background (Sano 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study of hybrid incompatibilities between Lycopersicon species identified several QTL that affect both male and female fertility, which could be due to pleiotropic effects of individual Dobzhansky-Muller interactions (Moyle and Graham 2005). Furthermore, a two-locus genetic incompatibility causes male and female sterility between the Indica and Japonica varieties of O. sativa (Kubo and Yoshimura 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several independent studies located loci responsible for spikelet sterility in the same area of chromosome 12 that was homologous to the ACL of P. simplex (Wu et al 1995;Wan et al 1996;Liu et al 2001). More recently Kubo and Yoshimura (2004) mapped in the same area the locus hsa1 responsible for hybrid breakdown in indica/japonica crosses. In all these cases the spikelet sterility was related to defective development of the embryo sac.…”
Section: Discussionmentioning
confidence: 99%